2017
DOI: 10.1002/cssc.201700398
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous Silica with Thick Framework for Steam‐Stable and High‐Performance Poly(ethyleneimine)/Silica CO2 Adsorbent

Abstract: Poly(ethyleneimine) (PEI)/silica has been widely studied as a solid adsorbent for post-combustion CO capture. In this work, a highly macroporous silica (MacS), synthesized by secondary sintering of fumed silica, is compared with various mesoporous silicas with different pore structures as a support for PEI. The silicas with large pore diameter and volume enabled high CO adsorption kinetics and capacity, because pore occlusion by the supported PEI was minimized. The steam stability of the silica structures incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 54 publications
2
72
0
1
Order By: Relevance
“…Generally, the low adsorbent stability necessitates the continuous addition of fresh adsorbents, which significantly increases the material cost for CO 2 capture. Amine-containing adsorbents are known to degrade via various chemical pathways including the oxidative degradation of amines 15 22 , 30 33 , urea formation under the CO 2 -rich atmosphere 21 25 , 33 35 , steam-induced degradation of the porous supports 20 , 26 28 , and irreversible adsorption of SO 2 29 , 37 , 38 . Aside from the oxidative degradation of amines, various solutions have been proposed for suppressing the degradation pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the low adsorbent stability necessitates the continuous addition of fresh adsorbents, which significantly increases the material cost for CO 2 capture. Amine-containing adsorbents are known to degrade via various chemical pathways including the oxidative degradation of amines 15 22 , 30 33 , urea formation under the CO 2 -rich atmosphere 21 25 , 33 35 , steam-induced degradation of the porous supports 20 , 26 28 , and irreversible adsorption of SO 2 29 , 37 , 38 . Aside from the oxidative degradation of amines, various solutions have been proposed for suppressing the degradation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, urea formation can be inhibited by selectively using secondary amines rather than primary amines 24 , 34 or injecting steam during adsorbent regeneration 14 , 22 , 23 , 28 . Steam-induced degradation can be solved by using porous supports with enhanced hydrothermal stability 26 28 . In addition, the amine poisoning by SO 2 can be avoided by employing advanced desulfurization unit before CO 2 capture 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Once the CO2 is desorbed, the steam is then condensed, leaving a stream of high purity CO2 for sequestration [42][43][44]. It is also noted that even if an alternative regeneration technique is used, the flue gas emitted from industrial plants, and other point sources, is not dry, containing between 3 -10 % H2O [44]. Thus, regardless of the regeneration technique employed, steam stability is still fundamental to practical sorbent design.…”
mentioning
confidence: 99%
“…Thus, regardless of the regeneration technique employed, steam stability is still fundamental to practical sorbent design. Several studies have focused on the stability of the amine species under these simulated steam stripping conditions [41][42][43][44]. We have previously shown that amine-functionalized mesocellular foam (MCF) is susceptible to structure degradation on steaming.…”
mentioning
confidence: 99%
See 1 more Smart Citation